Summary of readings in neurosurgery spine - Jafri Malin Abdullah (Siri kecetakan akademik, 2013)
: Spine is designed with an access to clear, incisive introduction to neurosurgery about the spine. The 10 chapters within the four parts present discussion on neurological problems related to spine as well as the diagnosis and management of the neurological disorders. With concise and convenient format, the text covers from succint introduction on neurosurgery and its problems like spinal disorders, to the diagnosis involved complete with the management of surgical procedures. This book is packed with practical information